After the Tsunami : Women and Land Reforms in Aceh - World Bank (Washington, DC, 2012)
On Boxing Day morning, 2004, a 9.3 magnitude earthquake struck the Indian Ocean. The quake unleashed a blast of energy and created a tsunami three stories high. The disaster claimed more than 228,000 lives, affected 2.5 million others and caused close to US $11.4 billion of damage in 14 countries. By far the highest price was paid by Aceh, where more people died than in all the other countries combined. In Banda Aceh, the capital of the province, the tsunami claimed nearly a third of the population. More than 800 km. of coastline was affected and close to 53,795 land parcels were destroyed. The land administration system sustained significant damage as documentation of land ownership was washed away. Physical boundary markers, including trees and fences, also disappeared. The tsunami and earthquake not only shattered housing and other coastal infrastructure, they also shook the foundations of Acehnese society and the social capital built up over decades.